Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1515/dmpt-2015-0046
|View full text |Cite
|
Sign up to set email alerts
|

Altered pharmacokinetics and pharmacodynamics of repaglinide by ritonavir in rats with healthy, diabetic and impaired hepatic function

Abstract: The significant difference in the PK/PD changes have been due to the increased plasma exposure and decreased total body clearance of repaglinide, which may be due to the inhibition of the CYP P450 metabolic system and organic anion-transporting polypeptide transporter by ritonavir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…17 However, disparities exist in the PK and PD parameters of antibacterial drugs between normal and infected animal models. 18 The PK-PD parameters of LVFX in combination with QGYD in infected models hold greater significance and clinical relevance compared to those in normal models. Therefore, we established a pneumonia model induced by MDR PA in rats and further investigated the PK-PD of LVFX alone or in combination with QGYD, providing a robust foundation for the combined use of Chinese and Western medicines in the treatment of MDR PA infections.…”
Section: Discussionmentioning
confidence: 99%
“…17 However, disparities exist in the PK and PD parameters of antibacterial drugs between normal and infected animal models. 18 The PK-PD parameters of LVFX in combination with QGYD in infected models hold greater significance and clinical relevance compared to those in normal models. Therefore, we established a pneumonia model induced by MDR PA in rats and further investigated the PK-PD of LVFX alone or in combination with QGYD, providing a robust foundation for the combined use of Chinese and Western medicines in the treatment of MDR PA infections.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the drug dose and treatment regimen, we mimicked a former study performed on insulin-resistant/type 2 diabetic rats, where repaglinide 0.5 mg/kg/day was administered for 2 weeks . Additionally, this dose was previously used experimentally in a pharmacokinetics and pharmacodynamics study performed on rats with normal, diabetic, and impaired hepatic function, while higher doses of repaglinide 1 and 2 mg/kg were tested for cardioprotective efficacy in an atherosclerotic rat model …”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported that ritonavir is a potent inhibitor of CYP3A4 (Kirby et al, 2011). The CYP3A inhibitory activity of ritonavir in rats has been reported with repaglinide, which is primarily metabolised by CYP3A4 in humans (Goud et al, 2016). Particularly pertinent to the current work, a pharmacokinetic interaction between the antimalarial quinine and ritonavir following concurrent administration has been reported, with a marked elevation in the plasma levels of quinine and a pronounced decrease in plasma concentrations of the major metabolite 3hydroxyquinine, which is primarily produced from quinine by CYP3A4 (Soyinka et al, 2010).…”
Section: Atovaquone-proguanil (Ap)mentioning
confidence: 99%